Digitalization of Web-Based Teaching Materials Through the Teams Games Tournament Learning Model to Improve Critical Thinking Skills of Elementary School Students in Civics Education (PKn) - Luqman Rohmad Maghribi; Eko Handoyo; Farid Ahmadi (Universitas Negeri Semarang, 2026)
The development of digital teaching materials has become a strategic priority in basic education reform in Indonesia, particularly as the Merdeka Belajar (Freedom to Learn) curriculum increasingly demands higher-order thinking skills from students at all school levels. However, Civics Education (PKn) in elementary schools is still characterized by rote memorization practices and teacher-centered instruction, resulting in underdevelopment of critical thinking skills. This study investigated the effectiveness of web-based digital teaching materials integrated with the Teams Games Tournament (TGT) cooperative learning model in improving fourth-grade elementary school students' critical thinking skills in Civics. A quasi-experimental design with a pre-test and post-test and a non-equivalent control group was used, involving 68 students from two parallel fourth-grade classes at SDN Pleburan 03 Semarang. The experimental group (n = 34) received instruction through a web-based digital teaching material platform incorporating TGT game mechanics, while the control group (n = 34) received conventional textbook-based instruction. Critical thinking skills were measured using a validated essay-based instrument aligned with the six dimensions of critical thinking: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Quantitative data were analyzed using independent sample t-tests and Mann-Whitney U tests, with effect sizes calculated using Cohen's d. Qualitative data were collected through classroom observations and teacher interviews to contextualize the quantitative findings. Results showed a statistically significant increase in critical thinking ability scores among students in the experimental group (M = 79.41, SD = 8.12) compared to the control group (M = 66.18, SD = 9.74), with a large effect size (Cohen's d = 1.47). Thematic analysis of the qualitative data identified three main themes: Digital Engagement as a Catalyst for Curiosity, Collaborative Competition as a Driver of Analytical Thinking, and Teacher Facilitation in Technology-Mediated Environments. These findings confirm that careful integration of digital instructional materials and TGT collaborative mechanisms is a pedagogically and contextually appropriate strategy for fostering critical thinking in elementary-level Citizenship Education in Indonesia.